2018
DOI: 10.1038/s41391-018-0089-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of family history of cancer on risk and mortality of second cancers in patients with prostate cancer

Abstract: SPCs were an important cause of death in patients with prostate cancer and family history was an important risk factor for SPCs. Prevention of SPC should be essential when prostate cancer survival rates are being improved and this could start by conducting a thorough assessment of family history at the time of prostate cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The high correlations suggest that skin cancer does not influence the formation of SPCs and thus SPCs appear to be autonomous from skin cancer which seems to resemble SPCs after prostate cancer. 4,6 The higher correlations after in situ than invasive SCC may be rationalized by in situ being a precursor stage of shorter life-span and size than invasive lesions. 8 If ranking was identical for FPC and SPC the correlation would be 1.00.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high correlations suggest that skin cancer does not influence the formation of SPCs and thus SPCs appear to be autonomous from skin cancer which seems to resemble SPCs after prostate cancer. 4,6 The higher correlations after in situ than invasive SCC may be rationalized by in situ being a precursor stage of shorter life-span and size than invasive lesions. 8 If ranking was identical for FPC and SPC the correlation would be 1.00.…”
Section: Discussionmentioning
confidence: 99%
“…However, our recent studies on SPC after prostate cancer suggested that SPCs were "autonomous" from prostate cancer because the frequencies of SPC correlated with the frequencies of these cancers as FPC and the risk of SPC was increased by the familial history of that cancer, irrespective of prostate cancer. 4,6 Moreover, the RRs for SPCs were equal in screening detected and other prostate cancer.…”
Section: Introductionmentioning
confidence: 91%
“…We also hypothesized that family history of cancer X increases the risk for cancer X to be an SPC, as has been observed for some other cancers. [17][18][19][20][21] We additionally tested if family history of skin cancer increases risk of second SCC after nonskin cancer. Some recent results on prostate, breast and ovarian cancers suggest that the cause of death in patients with SPC is often the SPC; 18,19,22 therefore, we assessed survival in patients with SCC who were diagnosed with SPC and whether survival is influenced by family history of SPC.…”
mentioning
confidence: 99%
“…Our study also has limitations. First, data regarding several important risk factors relevant to SPCs, such as smoking status [34,35] , family history of malignancies [36], and body weight [37], were not available from the SEER database, and thus could not be controlled when predicting the individual risk of developing SPCs. As our study cohorts were retrospectively collected within a long period, it is likely the risk of SPC was influenced by the secular trends of anticancer therapies.…”
Section: Discussionmentioning
confidence: 99%